Forecasting locations of forest fires in indonesia through nonparametric predictive inference with parametric copula: a case study - Amirah Hazwani Roslin,; Noryanti Muhammad,; Evizal Abdul Kadir,; Warih Maharani,; Hanita Daud, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Wildfires caused major damage and incurred high restoration costs. Despite numerous predictive studies in this field, wildfire management still had uncertainties. The machine learning technique was popular on this topic, but it portrayed gaps of non-generalisable and inaccuracy possibilities. This study intended to apply nonparametric predictive inference (NPI) with a parametric copula to predict the next wildfire location using the coordinate parameters. The NPI quantifies the uncertainties via imprecise probabilities, (